Assessment of the U.S. travelers’ destination image of Thailand - Sungkatavat, Sarinya (Kansas State University, 2013)
Thailand is one of the world’s most popular tourist destinations. However, it has not been successful in capturing and sustaining the U.S. travel market, one of the world’s top source markets by international tourism expenditure. The destination image (DI) is a key factor that affects destination selection, but there has been limited research exploring U.S. travelers’ DI of Thailand. Therefore, the purpose of this research was to measure U.S. travelers’ DI of Thailand and identify important attributes for U.S. travelers in terms of destination selection using mixed methods of qualitative and quantitative approaches. To explore American travelers’ DI of Thailand, personal interviews with 56 U.S. travelers were conducted at Suvarnabhumi Airport in Thailand. Maximum variation purposeful sampling was used to ensure diversity of the sample. One interviewer and a verifier ensured consistent and credible data collection and analyses. Data analyses included inductive, deductive and cross-case analyses. “Friendly People,” “Beaches and Islands,” and “Amazing” described Thailand's DI. First-time visitors had tourist attraction and activity-based images, while repeat visitors rated people and culture-related experience as top reasons for destination selection. Results from the qualitative study were used to identify common and unique attributes for the quantitative survey instrument. To access general perception of Thailand’s DI among U.S. travelers, an online survey was conducted with 522 international travelers including non-visitors (n=173), virtual-visitors (n=175) and visitors to Thailand (n=174). Descriptive statistics, ANOVA, and factor analyses were conducted. Of five factors that solidified the DI of Thailand, cultural attributes and local experiences represented Thailand’s DI the most. DIs were different among different types of visitors. Importance-Performance Analysis illustrated Thailand’s destination attributes and their importance for destination selection. For U.S. travelers, travel environment was the most important factor but had low performance. Thailand tourism organizations may use these findings for future marketing efforts toward the U.S. travel market.
Keywords: Destination image; Destination marketing; Thailand; U.S. travelers; Mixed methods; Management (0454); Marketing (0338)